Effect of GxE Interaction on Root Yield and Betacarotene Content of Selected Sweetpotato (Ipomoea batatas (L) Lam.) Varieties and Breeding Clones - Manrique, K.; Hermann, M. (2001)
A multilocational field trial involving nine sweetpotato clones of diverse origins was conducted across four different locations to investigate GxE interaction effects on commercial root yield and beta-carotene pigment content in roots. None of the high-yielding cultivars had satisfactory stability, according to biplots for total root yield based on the additive main effect and multiplicative interaction (AMMI) model. The lack of association of high root yield and stable performance suggests the need for further study to elucidate the nature of sweetpotato root-yield performance in response to varying agroecological conditions. Beta-carotene concentration increased in the roots of almost all tested clones when grown at a higher altitude. Clone SR 92.499-23 has been identified as the most efficient at producing and accumulating beta-carotene in relation to accumulation of root dry and fresh matter at high altitude.